2021
DOI: 10.1088/2057-1976/ac0547
|View full text |Cite
|
Sign up to set email alerts
|

Does participant’s age impact on tDCS induced fields? Insights from computational simulations

Abstract: Objective: Understanding the induced current flow from transcranial direct current stimulation (tDCS) is essential for determining the optimal dose and treatment. Head tissue conductivities play a key role in the resulting electromagnetic fields. However, there exists a complicated relationship between skull conductivity and participant age, that remains unclear. We explored how variations in skull electrical conductivities, particularly as a suggested function of age, affected tDCS induced electric fields. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 89 publications
1
5
0
Order By: Relevance
“…However, the effects of aging on conductivity may impact the estimated electric fields. One study found a reduction in intracranial electric field intensity due to a reduction in skull conductivity with age (McCann and Beltrachini, 2021). Thus, incorporating age-appropriate skull conductivity in the models may enhance the observed electric field magnitude reduction in the elderly population (due to the loss of grey matter volume), as shown in our study and others (Antonenko et al, 2021).…”
Section: Discussionsupporting
confidence: 78%
“…However, the effects of aging on conductivity may impact the estimated electric fields. One study found a reduction in intracranial electric field intensity due to a reduction in skull conductivity with age (McCann and Beltrachini, 2021). Thus, incorporating age-appropriate skull conductivity in the models may enhance the observed electric field magnitude reduction in the elderly population (due to the loss of grey matter volume), as shown in our study and others (Antonenko et al, 2021).…”
Section: Discussionsupporting
confidence: 78%
“…Finally, our individualized head models assumed known conductivities for all tissue types in the model. Literature shows that skull conductivity is highly variable ( McCann et al, 2019 ) and negative correlation with electric field strengths ( McCann and Beltrachini, 2021 ). Furthermore, we assumed CSF conductivity for the lesion, which might not represent all subjects in our sample, although commonly used ( Datta et al, 2011 , Minjoli et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In [101], a relation is found between certain tissue conductivities, like the skull and age. This was further investigated in [103], in which the effect of this age dependency on the tDCS fields is underlined. There are several more reasons for variability in tissue conductivities, such as the measurement method used, the tissue temperature, and inter-individual variations.…”
Section: Tissue Conductivity Uncertaintiesmentioning
confidence: 99%